Squatting revisited: comparison of haemodynamic responses in normal individuals and heart transplantation recipients. Issue 2 (August 1995) - Hanson, P.; Slane, P. R.; Rueckert, P. A.; Clark, S. V.
Abstract : BACKGROUND–Squatting produces a prompt increase in cardiac output and arterial blood pressure which is accompanied by an immediate decrease in heart rate and forearm vascular resistance. The rise in cardiac output and blood pressure has been attributed to augmented venous return from compression of leg veins, while the decreases in heart rate and forearm vascular resistance are probably due to activation of cardiopulmonary and arterial baroreflexes. Haemodynamic patterns in nine normal men and six heart transplant recipients during 2 min of squatting were examined to determine the role of cardiac innervation in the mediation of these responses. METHODS–Stroke volume was monitored by ensemble averaged thoracic impedance cardiography and blood pressure was determined with an Ohmeda fingertip plethysmograph. These techniques provided continuous measurements which were capable of detecting transient and non-steady state changes. Forearm blood flow was measured with venous occlusion plethysmography. Measurements were obtained after 3 min of quiet standing, immediately after squatting, and at 20, 60, and 120 s of sustained squatting. RESULTS–Both groups exhibited similar increases in stroke volume index (normal individuals 10.5 ml/m2; heart transplant recipients 10.3 ml/m2) and mean arterial pressure (normal individuals 8.5 mm Hg; heart transplant recipients 5.0 mm Hg) which were sustained throughout squatting. Each group also showed an initial decrease in peripheral resistance (normal individuals 3.6 units; heart transplant recipients 7.7 units) followed by a return to baseline values after 20 s. Heart rate decreased in normal individuals (10 beats/min) but was unchanged or minimally increased (2 beats/min) in heart transplant recipients. Forearm vascular resistance was conspicuously decreased in normal individuals (47.8 units) but only minimally (20.9 units) and not significantly in heart transplant recipients. CONCLUSIONS–The major haemodynamic responses to squatting (increased cardiac output and blood pressure) are similar in normal individuals and heart transplant recipients. These responses are primarily due to augmented venous return and are not altered by cardiac denervation. Both groups also exhibited a transient decline in peripheral vascular resistance which is most likely mediated by arterial baroreflexes activated by the acute rise in arterial blood pressure. The absence of a significant decrease in forearm vascular resistance in heart transplant recipients suggests that this response is partially mediated by cardiopulmonary or ventricular baroreflexes or that local forearm flow mediated vasodilatation remains impaired after heart transplantation.